Investigación para la elaboración del guión para documentales - Bejarano Ramos, Christian (2009)
It is very important to include research as a subject of study in the development of audiovisual projects that provide for the production of a documentary, which is why the aim of this article is to introduce an appropriate research methodology and objective for all those involved in conducting of an audiovisual product having the time as its limitation. As a result, one must learn to optimize time, human and technological resources in the process of a preliminary investigation, which will establish the limits in the search and thus select the most useful and necessary information that will lead to writing a first screenplay, and which in turn will help us to conceive the general idea of all the history that we want to present. The script will be born based on the data obtained in the research process. We must keep in mind that the script for a documentary is constantly being rewritten, which is why an analysis of how to handle writing the script for the documentary film are important issues to deal with the arduous task of producing an audiovisual project.